Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Lopez Torino, Sebastian (2019)
In short, on this study it will carry out a strategic diagnosis, then it will be analyzed the strategy formulation, also it will implement the most adequated strategy and finally, it will be able to strategic control with the purpose of directing and recommend the path to take.